1998
DOI: 10.1152/jn.1998.80.2.798
|View full text |Cite
|
Sign up to set email alerts
|

Two-Dimensional Saccade-Related Population Activity in Superior Colliculus in Monkey

Abstract: The two-dimensional distribution of population activity in the superior colliculus (SC) during saccadic eye movements in the monkey was estimated using radial basis functions. To make these ensemble activity estimates, cells in the deeper layers of the SC were recorded over much of the rostrocaudal (caudal to 3.8 mm from the rostral tip), mediolateral extent of this structure. The dynamic movement field of each cell was determined at 2-ms intervals around the time of saccades for a wide variety of horizontal a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

11
110
2

Year Published

2002
2002
2015
2015

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 119 publications
(123 citation statements)
references
References 38 publications
11
110
2
Order By: Relevance
“…The precise extent of the fixation zone is unknown-it is thought that cells with SCFN-like properties can be recorded in a region of the rostral SC ϳ0.5-0.7 mm long in the rostrocaudal direction (Munoz and Wurtz, 1995b;Anderson et al, 1998). We could not objectively assign SCFNs to specific positions within that region.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…The precise extent of the fixation zone is unknown-it is thought that cells with SCFN-like properties can be recorded in a region of the rostral SC ϳ0.5-0.7 mm long in the rostrocaudal direction (Munoz and Wurtz, 1995b;Anderson et al, 1998). We could not objectively assign SCFNs to specific positions within that region.…”
Section: Resultsmentioning
confidence: 99%
“…Regarding SCFNs, note that the extent of the collicular fixation zone is unknown and might encompass a rostral zone 0.5-0.7 mm long in the rostrocaudal direction (Munoz and Wurtz, 1995b;Anderson et al, 1998). We assumed that SCFNs lie within a zone 0 -0.5 mm long, and accordingly, we assigned to them random positions within this space along the horizontal meridian.…”
Section: Spatial Distribution Of Activity On Motor Map During Gaze Shmentioning
confidence: 99%
See 1 more Smart Citation
“…Buildup neurons are characterized by a slow buildup of activity before a saccade, in contrast to burst neurons, which are silent until right before a saccade. However, later evidence suggested that the dichotomy between buildup and burst neurons is not strict, and it may be more appropriate to consider them as a continuum (Anderson et al 1998;Munoz and Wurtz 1995a). With parameter values chosen here, model neurons in SC showed some buildup of activity before a saccade, and would fall in the middle of the spectrum from buildup to burst neurons.…”
Section: Model Neuronsmentioning
confidence: 94%
“…Two groups of signals can participate in the elaboration of this command and guide the saccades toward the transiently invisible moving target regardless of whether their trajectory is perturbed or not: (1) the target-motion-related signals that precede the blank interval and (2) the mnemonic signals that the target is expected to reappear and continue to move along the same path. A sort of interpolation would happen when the spread of target related activity (e.g., in the deep SC; Sparks et al, 1976;Anderson et al, 1998) merges with upcoming expected visual signals (Walker et al, 1995), "filling" the blank interval with a neural signal that would drive the gaze motor system.…”
Section: Introductionmentioning
confidence: 99%